Steigerung der Akzeptanz von intelligenter Videoüberwachung in öffentlichen Räumen - Krempel, Erik Ludwig (Karlsruher Schriften zur Anthropomatik / Lehrstuhl für Interaktive Echtzeitsysteme, Karlsruher Institut für Technologie ; Fraunhofer-Inst. für Optronik, Systemtechnik und Bildauswertung IOSB Karlsruhe, 2017)
The technical design of security systems has a high impact on its acceptance. To understand the influencing factors, an acceptance model for smart video surveillance is developed. To improve acceptance different technical components are designed and implemented. Lastly they are integrated into a prototype for fall detection in hospital environments and evaluated for the acceptance. The book combined theoretical work on understanding acceptance with practical work into developing new systems.